Evaluation of Enrollment Trends into Technical Education Programmes (2013-2023) In A Nigerian University Via Documentation Analysis - A. Auta, Mohammed; Anih, Ifechukwu Perpetual; Martin , Nnaemeka (Journal of Techno-Social, 2023)
This study is aimed at evaluating the enrolment trends into technical education programmes in a Nigerian University via Documentation Analysis. The study was conducted at Nnamdi Azikiwe University Awka, and it covered a period 2013-2023. A checklist titled “Technical Education Student Enrolment Trends Framework (TESET-F)” developed by the researcher was used to tabulate the data for ease of interpretation. Frequency counts and simple percentage were used as a tool for data analysis. Findings from the study indicated that that the enrolment trends into technical education programmes has witness an intermitted negative fluctuations in the last ten years to the extent that only 6% enrolment quota was filled in a particular academic year (2019/2020). The enrolment trends into technical education programme based on the three broad options favours electrical/electronic technology, building/woodwork technology and automobile/mechanical technology respectively. The enrolment of female gender into technical education is very low when compared with their male counterparts. The authors advocate on the need for concerted efforts to address the challenges and capitalize on the opportunities to improve the quality and relevance of technical education. Through this, universities in Nigeria can play a pivotal role in producing a highly skilled technical workforce that can contribute to the economic development and prosperity of the country.